Factors Associated Between House Sanitation Conditions and Incidence of Tuberculosis in Waepana Village Soa District Ngada Regency - Dhiu, Maria Ermelinda; Adu, Apris A.; Doke, Soni (Timorese Journal of Public Health, 2022)
Tuberculosis is an infectious disease caused by the bacterium mycobacterium tuberculosis. Most of the tuberculosis germs have attacked lung tissue, but can attack other organs in the human body.Early prevention efforts have been carried out, namely the BCG immunization package for toddlers. However, Indonesia is not 100% free from this disease. Mycobakterium tuberculosis is a rod-shaped bacterium that is grouped or called colonies. The environmental component itself includes the area of the house that is not proportional to the house that is not proportional to the occupants which will result in high density of housing, poor ventilation, type of house floor, type of house walls, lighting, temperature and humidity. Waepana village tuberculosis case data in 2019 amounted to 215 cases and in 2020 as many as 159 cases. The specific purpose of this study was to determine the relationship between occupancy density, ventilation area, floor type, wall type, lighting, temperature and humidity of the house with the incidence of tuberculosis in Waepana Village. The type of research used is an analytical survey with a case control research design. The location of the research in the village of Waepana which was carried out from August to September. The case population in this study were all tuberculosis patients, totaling 159 people and the control population were residents who lived in the village of Waepana with the criteria of not having tuberculosis, and the samples in this study were 74 people who were divided into two namely 37 case samples and 37 control samples. The data analysis used is univariate and bivariate analysis with chi-square test. The results of the study show that (p=0,000<0,05) there is relationship between residential density and the incidence of tuberculosis, (p=0,002<0,05) there is a relantionship between the type of floor with the incidence of tuberculosis, (p=0,000<0,05) there is a relantionship between the walls of the house with the incidence of tuberculosis, (p=0,001<0,05) there is a relationship between temperature and the incidence of tuberculosis. (p>0,433) there is no relationship between ventilation with the incidence of tuberculosis, (p>0,241) there is no relationship between lighting and the incidence of tuberculosis, (p>0,816) there is no relationship between humidity and the incidence of tuberculosis.